Combination of Anterior and Posterior Subcutaneous Internal Fixation for Unstable Pelvic Ring Injuries: The “Hula Hoop Technique” - Daniel Balbachevsky; Robinson Esteves Pires; Rodrigo Guerra Sabongi; Theóphilo Asfora Lins; Geiser de Souza Carvalho; Hélio Jorge Alvachian Fernandes; Fernando Baldy dos Reis (Journal of Trauma and Injury)
Unstable pelvic ring lesions are usually treated with internal fixation. In patients presenting clinical instability or soft tissue complication risk, external fixation is a safe treatment option. However, pin tract infection, insufficient biomechanical properties, difficulty sitting and changing decubitus are important drawbacks related to the treatment. The present study reports the association of anterior and posterior subcutaneous internal fixation by applying spine-designed implants on the pelvic ring disruption: supra-acetabular pedicle screws with an interconnecting rod (Infix), plus posterior transiliac fixation with the same system, which the authors have named the “Hula Hoop Technique”.